Desain Perancangan Troli Ergonomi Bagi Pekerja Material Handling UMKM Sigma Motor. - Kevin Ferdinand Andersona; Fuad Dwi Hanggara; Adi Nugroho (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2023)
The development of the industrial sector requires researchers to continue in innovate, from anindustrial management system, workflow design, to product innovation. There are so manyinnovations from products that are created to make it easier for users to do their work. But still,there are many MSMEs that still use human energy to do certain jobs, one of which is liftingand carrying loads manually or commonly referred to as Manual Materials. Handling (MMH).In one case of the MSMEs spare part distributor